The Influence of Preconception Preparation on the Structural Restructuring of the Endometrium in Women with Chronic Endometritis and Infertility (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In recent years, the interest of researchers in the specific nosology of pelvic inflammatory diseases (PID) - chronic endometritis - has increased significantly, which is explained by the presence of a whole set of problems related to etiopathogenesis, diagnostic criteria and characteristics. Approaches to the treatment of this pathology. The chronic inflammatory process in the endometrium is one of the main causes of menstrual disorders, abortion, infertility, failed IVF attempts, endometrial hyperplastic processes and sexual dysfunction. The need to continue to develop advanced methods of diagnosis and treatment of chronic endometritis is related to its medical and social importance, since the majority of patients with this pathology are women of active reproductive age [2, 4, 5, 7, 11, 13, 14 ].